Differential Regulation of TGF-β/Smad Signaling in Hepatic Stellate Cells between Acute and Chronic Liver Injuries - Yoshida, Katsunori; Matsuzaki, Koichi (Frontiers in Physiology, 2012)
Current evidence suggests that regulation of extracellular matrix (ECM) accumulation by fibrogenic TGF-β and PDGF signals involves different mechanisms in acute and chronic liver injuries, even though hepatic stellate cells (HSC) are the principal effecter in both cases. As a result of chronic liver damage, HSC undergo progressive activation to become myofibroblasts (MFB)-like cells. Our current review will discuss the differential regulation of TGF-β signaling between HSC and MFB in vitro and in vivo. Smad proteins, which convey signals from TGF-β receptors to the nucleus, have intermediate linker regions between conserved Mad homology (MH) 1 and MH2 domains. TGF-β type I receptor and Ras-associated kinases differentially phosphorylate Smad2 and Smad3 to create COOH-terminally (C), linker (L), or dually (L/C) phosphorylated (p) isoforms. After acute liver injury, TGF-β and PDGF synergistically promote collagen synthesis in the activated HSC via pSmad2L/C and pSmad3L/C pathways. To avoid unlimited ECM deposition, Smad7 induced by TGF-β negatively regulates the fibrogenic TGF-β signaling. In contrast, TGF-β and PDGF can transmit the fibrogenic pSmad2L/C and mitogenic pSmad3L signals in MFB throughout chronic liver injury, because Smad7 cannot be induced by the pSmad3L pathway. This lack of Smad7 induction might lead to constitutive fibrogenesis in MFB, which eventually develop into accelerated liver fibrosis.